2003
DOI: 10.1109/ted.2003.812490
|View full text |Cite
|
Sign up to set email alerts
|

MEMS fingerprint sensor immune to various finger surface conditions

Abstract: This paper describes a new fingerprint sensor that detects the topography of finger ridges and valleys. We propose a microelectromechanical systems (MEMS) cavity structure for the pixels arrayed on the sensor surface and a fabrication process that stacks the cavity structures on a CMOS LSI. A thin film on top of the cavity structures is bent by finger ridges mechanically, which is detected by the sensing circuits below them electronically. Based on an analytical model, we designed a cavity structure suitable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Also, the integration density of organic-FET is much lower than the present silicon technology, and its long term reliability in force sensor applications has not yet been demonstrated. Silicon-MEMS tactile imagers, integrating micro pressure sensor array (Sugiyama et al, 1990) or micro force-sensor array, have been reported earlier ; (b); Kobayashi et al, 1990;Souza & Wise, 1997;Mei et al, 1999;Mei et al, 2000;Sato et al, 2003;Charlot et al, 2004). This type of sensors can reduce the number of electronic signal wires by integrated switching matrix fabricated using CMOS technology (Doelle et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Also, the integration density of organic-FET is much lower than the present silicon technology, and its long term reliability in force sensor applications has not yet been demonstrated. Silicon-MEMS tactile imagers, integrating micro pressure sensor array (Sugiyama et al, 1990) or micro force-sensor array, have been reported earlier ; (b); Kobayashi et al, 1990;Souza & Wise, 1997;Mei et al, 1999;Mei et al, 2000;Sato et al, 2003;Charlot et al, 2004). This type of sensors can reduce the number of electronic signal wires by integrated switching matrix fabricated using CMOS technology (Doelle et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…MEMS devices have been the recent interest in fingerprint acquisition systems such as the works done by Souza and Wise 1997;Charlot et al 2004;Takao et al 2004;Knapp 2004;Fojimori et al 2005;Sato et al 2003Sato et al , 2004Sato et al , 2005. MEMS Capacitive fingerprint sensors offer many advantages over existing technologies for biometrics extraction.…”
Section: Introductionmentioning
confidence: 99%
“…They are a promising alternative due to low power consumption, non bulky structures and no turn on temperature drifts. Recent prototypes have tried to fabricate the sensor on flexible substrate (Takao et al 2004), improve sensitivity (Sato et al 2004), make the device immune to finger surface condition (Sato et al 2003), make a single chip sensor (Fojimori et al 2005), or other modifications but most are not commercially manufactured which means there are still rooms for improvements on price and performance.…”
Section: Introductionmentioning
confidence: 99%
“…There are various fabrication processes have been exploited to implement the tactile sensors. For instance, the silicon-based process [1][2][3][4][5][6], such as the CMOS and bulk micromachining processes, and the nonsilicon-based process [7][8][9][10][11][12], such as the polymer process. As a result, the variety as well as the performance of the tactile sensor has been significantly improved by the fabrication processes.…”
Section: Introductionmentioning
confidence: 99%